Prevalence of Early Childhood Caries (ECC) in Children Aged 2–6 years in the Highlands and Lowlands of West Java - Sofian MA; Setiawan AS; Hamdani AM; Pratidina NB; Suwargiani AA (Clinical, Cosmetic and Investigational Dentistry)
Maharani Alika Sofian,1 Asty Samiaty Setiawan,2 Ardena Maulidia Hamdani,2 Naninda Berliana Pratidina,3 Anne Agustina Suwargiani2 1Undergraduate Programme in Dentistry, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia; 2Department of Dental Public Health, Faculty of Dentistry, Universitas Padjadjaran, Bandung, Indonesia; 3Department of Pediatric Dentistry, Faculty of Dentistry, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Asty Samiaty Setiawan, Email asty.setiawan@unpad.ac.idBackground: Early Childhood Caries (ECC) is a major dental health issue that affects children worldwide. The prevalence of ECC can vary between regions, and understanding these differences is essential for targeted public health interventions. This study aimed to compare the prevalence of ECC in children aged 2– 6 years from the highland and lowland areas of West Java.Methods: The research method used a cross-sectional study. Data collection was conducted in Rancabali District, Bandung Regency as a highland with an altitude of 1600 masl and Cijulang District, Pangandaran Regency as a lowland with an altitude of 30 masl. Sampling was determined using purposive sampling technique with a total sample of 201 children consisting of 98 children in the highlands and 103 children in the lowlands. Data were analysed using the Chi-Square test.Results: The prevalence of early childhood caries in children aged 2– 6 years in Bandung Regency was 91.8% with a mean def-t index of 10.03 and in children aged 2– 6 years in Pangandaran Regency was 96.1% with a mean def-t index of 10.74. The mean value of the def-t index in both regions is in the very high category according to WHO. Chi-square test results with a p-value > 0.05, namely 0.201, showed that there was no significant difference between the prevalence of ECC in children aged 2– 6 years in Bandung Regency and Pangandaran Regency.Conclusion: There is no difference in the prevalence of early childhood caries in children aged 2– 6 years in the highlands and lowlands of West Java.Keywords: early childhood caries, ECC, highlands, lowlands, prevalence